Birth weight and large for gestational age trends in offspring of pregnant women with gestational diabetes mellitus in southern China, 2012-2021 - He, Li-Rong; Yu, Li; Guo, Yong (Frontiers in Endocrinology, 2023)
Background: With increasing prevalence of gestational diabetes mellitus (GDM) and changing management of GDM in pregnancy, it is imperative to understand the evolution of its current outcomes. The present study aimed to explore whether birth weight and large for gestational age (LGA) trends in women with GDM have changed over time in southern China. Methods: In this hospital-based retrospective study, all singleton live births for the period 2012 to 2021 were collected from the Guangdong Women and Children Hospital, China. GDM was diagnosed following the criteria of the International Association of Diabetes and Pregnancy Study Group. The cutoff points for defining LGA (>90th centile) at birth based on INTERGROWTH-21st gender-specific standards. Linear regression was used to evaluate trends for birth weight over the years. Logistic regression analysis was used to determine the odds ratios (ORs) of LGA between women with GDM and those without GDM. Results: Data from 115097 women with singleton live births were included. The total prevalence of GDM was 16.8%. GDM prevalence varied across different years, with the lowest prevalence in 2014 (15.0%) and the highest prevalence in 2021 (19.2%). The mean birth weight displayed decrease in women with GDM from 3.224kg in 2012 to 3.134kg in 2021, and the z score for mean birth weight decreased from 0.230 to -0.037 (P for trend < 0.001). Among women with GDM, the prevalence of macrosomia and LGA reduced significantly during the study period (from 5.1% to 3.0% in macrosomia and from 11.8% to 7.7% in LGA, respectively). Compared to women without GDM, women with GDM had 1.30 (95% CI: 1.23 - 1.38) times odds for LGA, and the ORs remained stable over the study period. Conclusions: Among offspring of women with GDM, there are decreased trends of birth weight in parallel with reductions in LGA prevalence between 2012 and 2021. However, the risk of LGA in women with GDM remains stable at relatively high level over the 10-year period, and efforts are still needed to address regarding causes and effective intervention strategies.